Influence of biomineralization on a profile of a tropical soil affected by erosive processes (2015)
Most of the soils of tropical countries, especially those in South America and Africa, are affected by erosion processes. As a result, researchers in the field of geotechnical engineering, specifically in the context of "biotechnology" or "bioengineering", have been investigating the use of microorganisms to improve the geotechnical properties and stability of soils. Using this approach, this work was developed to analyze the effects of the implementation of a calcium carbonate precipitating nutrient in native microbiota on the mitigation of erosion processes in a tropical soil profile. The methodology used in this research consisted of collecting undisturbed samples in a soil profile located in an area affected by erosion processes. In such samples, the native bacteria were identified, and it was determined that the nutrient B4 induced the precipitation of calcium carbonate. Subsequently, soil samples were characterized physically, chemically, mineralogically and mechanically in their natural state and after the addition of the nutrient. The tests were performed at least fifteen days after treatment with the nutrient. It was concluded that the use of the nutrient B4 enabled the native bacteria present in the soil to precipitate calcium carbonate, resulting in improvements in the physical, chemical, mineralogical and mechanical properties of the soil, which allowed for the mitigation of erosion processes that characterize the soil profile studied. The conclusions derived from the study apply not only to other tropical soil profiles subjected to erosion but also to improvements of the geotechnical behavior of soils in general.